2017
DOI: 10.1530/erc-17-0006
|View full text |Cite
|
Sign up to set email alerts
|

Gestational high-fat diet and bisphenol A exposure heightens mammary cancer risk

Abstract: In utero exposure to bisphenol A (BPA) increases mammary cancer susceptibility in offspring. High-fat diet is widely believed to be a risk factor of breast cancer. The objective of this study was to determine whether maternal exposure to BPA in addition to high-butterfat (HBF) intake during pregnancy further influences carcinogen-induced mammary cancer risk in offspring, and its dose–response curve. In this study, we found that gestational HBF intake in addition to a low-dose BPA (25 µg/kg BW/day) exposure inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 60 publications
1
43
0
2
Order By: Relevance
“…An abnormal increase in insulin secretion in the lower BPA group is likely to eventually lead to exhaustion of 50 This is further supported by data from human and animal studies showing that a constant increase in insulin secretion can lead to mitochondrial dysfunction and endoplasmic reticulum stress, which leads to cellular injury and a progressive decline in β-cell function (i.e., βcell exhaustion). 51,52 Furthermore, the third-generation animals of the current study may display an altered metabolic response, if challenged by a second insult such as a high-fat diet as reported in pancreas 53 and other target tissues like mammary gland, sperm and liver [54][55][56] of the first-generation offspring. This requires further investigation.…”
Section: Discussionmentioning
confidence: 85%
“…An abnormal increase in insulin secretion in the lower BPA group is likely to eventually lead to exhaustion of 50 This is further supported by data from human and animal studies showing that a constant increase in insulin secretion can lead to mitochondrial dysfunction and endoplasmic reticulum stress, which leads to cellular injury and a progressive decline in β-cell function (i.e., βcell exhaustion). 51,52 Furthermore, the third-generation animals of the current study may display an altered metabolic response, if challenged by a second insult such as a high-fat diet as reported in pancreas 53 and other target tissues like mammary gland, sperm and liver [54][55][56] of the first-generation offspring. This requires further investigation.…”
Section: Discussionmentioning
confidence: 85%
“…High mRNA expression levels of MAGEE1 were significantly associated with improved RFS in grade I and basal-like 2 breast cancer, but also with worse RFS in grade III and mesenchymal breast cancer; high mRNA expression levels of MAGEE2 were significantly associated with improved RFS in basal, lymph node-negative and mesenchymal stem-like breast cancer, but also with worse RFS in TP53 wild-type breast cancer. MAGEE2 expression has been reported to be associated with poor OS in The Cancer Genome Atlas human breast cancer cohort (n=1,082) (49). In general, these findings indicated that MAGEE2 was closely associated with the occurrence and development of breast cancer, particularly in TP53 wild-type breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary exposure to BPA in the Agouti viable yellow (A(vy)) mouse model has been shown to hypomethylate metastable epialleles, an effect that can be counteracted with dietary supplementation of methyl donors or genistein ( 61 ). According to further evidence from animal models, antenatal and perinatal BPA exposure has been found to lead to specific epigenetic changes, resulting, among the others, in impaired stress response ( 62 ) and higher rates of mammary cancer ( 63 ); this contributes to highlight the clinical burden associated with chemical food contamination.…”
Section: Effect Of Maternal Nutrition On Pregnancy Epigenetics and Fementioning
confidence: 99%